2010
DOI: 10.1021/jf101034a
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Carrot (Daucus carota) Microstructure on Carotene Bioaccessibilty in the Upper Gastrointestinal Tract. 1. In Vitro Simulations of Carrot Digestion

Abstract: Studies investigating carotene bioaccessibility (release from the food matrix to a solubilized form) directly from plant material during the process of digestion are scarce, mainly due to the difficulties associated with obtaining such material. Therefore, this paper examines the relationship between tissue microstructure and carotene bioaccessibility using an in vitro digestion model. Dietary oil provides a pool for the initial solubilization. Therefore, carotene partitioning into an emulsified oil phase was … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
59
1
1

Year Published

2011
2011
2018
2018

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 84 publications
(69 citation statements)
references
References 38 publications
(75 reference statements)
8
59
1
1
Order By: Relevance
“…At the multicellular level, many sources of food carbohydrate are swallowed in the form of plant tissue fragments in which cell walls, and multiple overlying layers of cells, may act as partial barriers to both digestive enzyme penetration into, and carbohydrate diffusion out of the fragment or particle. In fruits, cereal kernels, nuts and pulses, tissue structure may influence the availability of carbohydrate and other nutrients (Mandalari et al 2008;Palafox-Carlos et al 2011;Tydeman et al 2010a;Tydeman et al 2010b).…”
Section: Cell and Tissue Levelmentioning
confidence: 99%
See 1 more Smart Citation
“…At the multicellular level, many sources of food carbohydrate are swallowed in the form of plant tissue fragments in which cell walls, and multiple overlying layers of cells, may act as partial barriers to both digestive enzyme penetration into, and carbohydrate diffusion out of the fragment or particle. In fruits, cereal kernels, nuts and pulses, tissue structure may influence the availability of carbohydrate and other nutrients (Mandalari et al 2008;Palafox-Carlos et al 2011;Tydeman et al 2010a;Tydeman et al 2010b).…”
Section: Cell and Tissue Levelmentioning
confidence: 99%
“…Recent detailed studies of the release of nutrients from nut fragments have shown that cell walls formed a very effective barrier against the intestinal environment (Mandalari et al 2008;Palafox-Carlos et al 2011;Tydeman et al 2010a;Tydeman et al 2010b). Mandalari et al (2010) showed that after 3 h of simulated gastric plus duodenal digestion of almond fragments, the intracellular contents had been lost from only the first layer of the cells, at the fracture surface.…”
Section: B Chopping/cuttingmentioning
confidence: 99%
“…Lemmens et al (2011b) could model the increase in β-carotene bioaccessibility (release from the matrix) during thermal processing (90-120°C) of carrot particles (500-4000 μm) as a function of time by a fractional conversion model. Conversely, Tydeman et al (2010) stated that particle size reduction is more important than heat treatment to enhance β-carotene bioaccessibility. In the context of improved β-carotene bioaccessibility in thermally processed carrot products, β-eliminative depolymerization of pectin should be considered.…”
Section: Effect Of Processing On β-Carotene Bioaccessibilitymentioning
confidence: 99%
“…Several of the most advanced in vitro digestion systems (Ferrua & Singh, 2010;Minekus, Marteau, Havenaar, & Huis in 't Veld, 1995;Tharakan et al, 2010;Tydeman et al, 2010) were not included by the authors in the article. Did they use Web of Science, Scopus, Pubmed or Google Scholar?…”
Section: Sirmentioning
confidence: 99%
“…Last but not the least, the authors seem to rely too much on a single reference that itself is a review on in vitro digestion models and was published nearly 20 years ago (Boisen & Eggum, 1991) while they neglected the recent advances and applications in the field (Anson, Havenaar, Bast, & Haenen, 2010;Anson, Selinheimo et al, 2009;Anson, van den Berg, Havenaar, Bast, & Haenen, 2009;Blanquet et al, 2004;Blanquet-Diot, Soufi, Rambeau, Rock, & Alric, 2009;Dupont et al, 2010;Ferrua & Singh, 2010;Mandalari, Adel-Patient et al, 2009;Mandalari, Mackie, Rigby, Wickham, & Mills, 2009;Mandalari et al, 2010;Marteau, Minekus, Havenaar, & Huis in 't Veld, 1997;Mercuri, Lo Curto, Wickham, Craig, & Barker, 2008;Minekus, Marteau, Havenaar, & Huis in 't Veld, 1995;Mitea et al, 2008;Tharakan et al, 2010;Tydeman et al, 2010;Verwei, Freidig, Havenaar, & Groten, 2006;Verwei et al, 2003). Therefore, unfortunately the overview given by Hur et al in their review article does not represent the state-of-the-art of in vitro digestion models.…”
Section: Sirmentioning
confidence: 99%